Use of a Human Artificial Chromosome for Delivering Trophic Factors in a Rodent Model of Amyotrophic Lateral Sclerosis - Yasuhiro Watanabe; Yasuhiro Kazuki; Kanako Kazuki; Mitsutaka Ebiki; Mami Nakanishi; Kazuomi Nakamura; Miho Yoshida Yamakawa; Hiroyuki Hosokawa; Tetsuya Ohbayashi; Mitsuo Oshimura; Kenji Nakashima (Elsevier, 2015)
A human artificial chromosome (HAC) is maintained as an episome within a cell and avoids random integration into the host genome. It can transfer multiple and/or large transgenes along with their regulatory elements thereby resembling native chromosomes. Using this HAC system, we established mesenchymal stem cells (MSCs) that simultaneously expressed hepatocyte growth factor, glial cell line-derived neurotrophic factor, and insulin-like growth factor 1, termed HAC-MSCs. This cell line provides an opportunity for stable transplantation and thorough analyses. We then introduced the cells for the treatment of a neurodegenerative disorder, amyotrophic lateral sclerosis. The HAC-MSCs were transplanted via the fourth cerebral ventricle (CV) or intravenous (i.v.) infusion at various ages of recipient mice. Littermate- and sex-matched mice underwent a sham procedure. Compared to the controls, there was an encouraging trend of increased life span via CV transplantation and delayed onset in i.v. infusion 60 days after transplantation. Further, we confirmed a statistically significant increase in life span via CV transplantation at 100 days. This effect was not seen in mice transplanted with MSCs lacking the HAC. We successfully enhanced the trophic potential of the MSCs using the HAC. This strategy could be a promising direction for the treatment of neurodegenerative disorders.